Legal Regulation of Pharmacy Operation prior to 1918 - Petlina, Tetiana V. (Teisė, 2024)
The article aims to investigate the question of the legal regulation of the field of pharmacy in the 17th – early 20th centuries, which is of relevance in the history of medicine and pharmacy as one of the forerunning cross-disciplinary branches in the historical-legal research. In the article, academic literature is used as a primary source of information, as well as the laws and the decisions of the Governing Senate in pharmacy cases before 1918.
Keywords: pharmacy law; pharmacies; medical law; history of medical law; pharmacy legislation